Comparison of Inflation and Economic Growth as Monetary Policy Targets in Indonesia for The Period 2002-2021 - Mughni BW Pradikta; Retno Agustina Ekaputri; Esti Pasaribu (Faculty of Economics, Universitas Sriwijaya, 2023)
This study aims to analyze the effectiveness of Indonesian monetary policy form 2002-2021 by comparing the ultimate target of Indonesian monetary policy as measure of the effectiveness of transmission mechanism in this research, which is GDP and Inflation. The data used in this study is secondary data, and the form data is quarterly data. Gross Domestic Product (GDP), Inflation Rate, BI Rate, and money supply are among the time series data. The Multiple Linear Regressions analysis tool was used in this study study to examine how the real sector responds to government policies in the long term. As a result, monetary policy has a faster response in GDP than the target inflation rate.